330 Comparing Outcomes in Right Versus Left Kidney Transplantation; A Systematic Review and Meta-Analysis. (12th October 2021) - Carolan, C; Tingle, S; Thompson, E; Sen, G; Wilson, C
Abstract: Introduction: Transplantation of right kidneys can pose technical challenges due to the short right renal vein. Whether this results in inferior outcomes remains controversial. Method: We used Healthcare Database Advanced Search (HDAS) to identify relevant studies. Two authors independently reviewed each study. Statistical analyses were performed using random effects models and results expressed as HR or relative risk (RR) with 95% confidence intervals. Subgroup analyses were performed in kidneys from deceased donors (DD) and living donors (LD). Results: 35 studies (257, 429 participants) were identified. Both deceased and living donor right kidneys were at increased risk of delayed graft function (DGF; RR = 1.10[1.07-1.12] p < 0.00001). In absolute terms, for each 100 kidney pairs of DD kidneys transplanted there are 2.72 (1.67-3.78, p < 0.00001) excess episodes of DGF in right kidneys. Graft thrombosis rate was also significantly higher in right kidneys, in both DD and LD settings (RR = 1.55[1.41-1.69] p < 0.00001). Compared to DD left kidneys, DD right kidneys were at significantly higher risk of graft failure due to technical causes (RR = 1.54[1.25-1.90], P < 0.0001). The two largest DD studies (179, 124 participants) found right kidneys to have significantly poorer graft survival; time-varying analyses demonstrated this was caused by early graft losses within the first year. There was no evidence that laterality alters long term graft survival in LD or DD. Conclusions: Right kidneys are at increased risk of early complications in both DD and LD settings, although the absolute effects are small. Improved vascular reconstruction techniques for the right renal vein, which avoid detrimental impacts on ischaemia times, are essential.